KESATUAN â€œPEMIKIRANâ€ DAN â€œPERASAANâ€ DALAM 20 PUISI ROMANTIK KARYA WILLIAM WORDSWORTH - ARBIE, DANTI DAMAYANTI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT The reseacrh which entitled â€œKesatuan Pemikiran dan Perasaan dalam 20 Puisi Romantik karya William Wordsworthâ€ aims at analyzing how the â€œthoughtâ€ and â€œfeelingâ€ are united in the 20 poems of Wordsworth namely I Wandered Lonely as a Cloud, The Rainbow, A Complaint, A Character, A Night Thought, A Sketch, A Perfect Woman, Surprised by Joy, The Virgin, Mutability, Speak, It Is a Beauteous Evening Calm and Free, Is There A Power That Can Sustain and Cheer, The Forsaken, Sweet Was the Walk, Most Sweet It Is, Admonition, Composed During a Storm, To Sleep and Minstrels. In terms of â€œmethodologyâ€ the writer moves through the steps of Concept Introduction., Theory and Approaches used, the Method of both Data Collection and Data Analysis applied and Research Findings report as a conclusion. Concepts to be emphasized are â€œthoughtâ€ and â€œfeelingâ€ regocnizable to most English Literature Romantic group of literary people as the ones belong to William Wordsworth through an approach namely Intrinsic one, which basically apply the Figures of Speech, such as Simile, Metaphor, Personification, Hyperbole, Apostrophe including relevant Dictions by Lawrence Perrine found in his book titled â€œSound and Senseâ€. In terms of Data Collection, a method namely â€œContent Analysisâ€ is applied to go through the content of the 20 poems selected to be analyzed to catch the comprehension of them. Data analysis follow to unite â€œthoughtâ€ and â€œfeelingâ€ found in those 20 poems of Wordsworth . The research findings show that there is a strong â€œunityâ€ between those 2 aspects which are â€œthoughtâ€ and â€œfeelingâ€. Â Keywords: Lawrence Perrine, Figures of Speech, Simile, Metaphor, Personification, Apostrophe, Symbol, Hyperbole, Diction.